2015
DOI: 10.3109/00016489.2014.979437
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of congenital aural atresia – is it still justified?

Abstract: For 90% of the patients in group 1 and 79% of the patients in group 2, the postoperative ABG was within 0 and 30 dB. The most common complications were recurrent infection, lateralization of the tympanic membrane, and restenosis of the ear canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…Sometimes the inner ear can be affected too [Schuknecht, ]. Overall, patients with unaffected middle ear and hearing ossicles, have best surgical outcomes [Cremers et al, ; Schuknecht, ; Jahrsdoerfer et al, ; Oliver et al, ; Edfeldt and Strömbäck, ; Moss et al, ]. The patient presented here had a total bony atresia over part of the external meatus, resembling a type IIA aural atresia in the Altmann–Cremers classification [Cremers et al, ].…”
Section: Discussionmentioning
confidence: 88%
“…Sometimes the inner ear can be affected too [Schuknecht, ]. Overall, patients with unaffected middle ear and hearing ossicles, have best surgical outcomes [Cremers et al, ; Schuknecht, ; Jahrsdoerfer et al, ; Oliver et al, ; Edfeldt and Strömbäck, ; Moss et al, ]. The patient presented here had a total bony atresia over part of the external meatus, resembling a type IIA aural atresia in the Altmann–Cremers classification [Cremers et al, ].…”
Section: Discussionmentioning
confidence: 88%
“…The average number of hospital admissions during the first postoperative year was 10 (range [5][6][7][8][9][10][11][12][13][14][15][16][17] per patient. At the end of the follow-up, the cumulative number of visits was 21 (range 7-39).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in 12 patients, the mean postoperative PTA was 18 dB HL better than preoperatively [6]. Edfeldt et al (2015) reported that over 80% of their 100 atresia patients obtained an ABG less than 30 dB HL. Nadaraja et al (2013) performed a systematic review to compare the hearing results of atresia surgery and osseointegrated bone conduction device in CAA patients [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ряд авторов предлагают использовать передний доступ; при этой технике создание трепанационной полости борами начинают в области предполагаемой проекции наружного слухового прохода отступя от височно-нижнечелюстного сустава и ниже уровня средней черепной ямки. Наиболее распространен трансмастоидалный доступ с широким вскрытием антрума и аттика, который позволяет минимизировать такие послеперационные осложнении, как рестеноз канала, инфицирование среднего уха и повреждение лицевого нерва [20,21].…”
Section: результаты и обсуждениеunclassified